العدول عن التعاقد بالعربون و الضرر الناتج عنه - عون، عصام محمد الصويعي; صالح، أحمد زكي (عبد الفتاح محمود ادريس, 2014)
تناولت هذه الدراسة ظاهرة العدول عن التعاقد بالعربون والضرر الناتج عنه الآثار التي تتركها على المتعاقدين جراء العدول والمضي في إتمام عملية البيع مركزة على تحليل الجوانب القانونية في القانون المدني الليبي وبعض القوانين المشابهة له، وكذلك الاهتمام بكيفية معالجة الضرر والآثار المترتبة عنه بشكل علمي منهجي يتعدى النظر إلى المشكلة بشكل سطحي، ويكون أعمق في بحث أسبابها بشكل جدري، ثم اقتراح ما يصلح للتعامل مع المشكلة، وخلص البحث إلى ضرورة التركيز على تطوير وتحديث النصوص القانونية التي تتماشى مع ما هو مطبق واقعيا للبيع بالعربون، والاهتمام بتطبيق الجانب الشرعي في هذه المسألة وذلك لخلق علاقة تعامل تجاري على أساس شرعي وقانوني يخدم أطراف التعاقد. This study examined the phenomenon of reverse contracting the deposit, and the damage caused by the effects they are having on the contractors by the reverse and proceed with the completion of the sales process focused on the analysis of the legal aspects of the Libyan Civil Code and some laws similar to him, as well as attention to how to deal with the damage and the consequences of it in a scientific systematic exceed to look at the problem superficially, and be deeper in search causes a pox, and then propose what is fit to deal with the problem, the research found the need to focus on the development and modernization of the legal texts that are in line with what is applied is actually for sale the deposit, and interest in the application of forensic aspect in this issue so as to create a commercial relationship deal on the basis of a legitimate and legal contracting parties to serve.
Keywords: عقود البيع -- الأحكام الفقهية -- الأحكام القانونية